The Ablation of Thyroid Nodule’s Afferent Arteries Before Radiofrequency Ablation: Preliminary Data - Offi, Chiara; Garberoglio, Sara; Antonelli, Giovanni; Esposito, Maria Grazia; Brancaccio, Umberto; Misso, Claudia; D’Ambrosio, Edoardo; Pace, Daniela; Spiezia, Stefano (Frontiers in Endocrinology, 2021)
Induced radiofrequency thermal ablation is the cytoreductive treatment of symptomatic benign thyroid nodules, metastatic and recurrent thyroid tumors and papillary thyroid microcarcinomas. It is a safe and effective alternative to surgery and it allows to obtain satisfactory results in terms of volumetric reduction of the nodule with significant improvement in the quality of life. The trans-isthmic approach and the moving shot technique are the two basic techniques; however, an advanced technique, artery-first feeding radiofrequency ablation, has been developed and validated. We have prospectively included 29 consecutive patients who have undergone radiofrequency ablation (Group A) or artery-first vRFA (Group B). All included patients had a diagnosis of benign nodular goiter and they underwent a single session of radiofrequency ablation. All patients followed a follow-up program at 1-month, 3-months and 6-months. Continuous variables (age, TSH-value, basal nodule volume, used-Joule, time in second of the procedure, nodules’ volume at 1-, 3- and 6-months of follow-up and percentage of volume reduction at 1-, 3- and 6-months of follow-up) were described as mean, standard deviation and range, while categorical variables (gender, nodule structure and nodule vascularization) were described as number of cases and percentage. Independent samples t-test were performed to compare the continuous variables. A propotion's Test was applied to the categorical variables. The Fisher’s exact test was used to analyze the gender. Statistical significance was considered in case of p-value <0.05. Solid structure and spongiform structure showed statistic differences with p-values of 0.022 and 0.023 respectively between two groups. The percentage of reduction at 1-month did not show a significant difference between two groups; instead, the percentage of volume reduction was decreased mostly in the Group B at 3-months and 6-months of follow-up with a p-value of 0.003 and 0.013, respectively. The Joules/energy used showed a statistically significant difference (p-value=0.05), more energy must be used in vascular radiofrequency ablation. These data allow us to hypothesize that vRFA may improve the procedure effectiveness, allowing for a reduction in volume more quickly. They were preliminary but promising results, clearly a larger series of cases and prolonged follow-up are needed to clarify and confirm our observations.